Pengaruh Penggunaan Media Loose Parts dalam Pembelajaran terhadap Kreativitas Anak Usia 5–6 Tahun - Agnes Agusta Kaes Faot; Credo G. Betty; Yohana Yuniati; Gokma N. Tampubolon (Faculty of Education and Teacher Training of UINSI Samarinda, 2026)
This study aims to determine the effect of using loose parts media in learning on the creativity of 5–6-year-old children at PAUD Yayasan Pedati Indonesia (YPI) Bimbi Enoneontes, Kuatnana District. This study employed a quantitative approach with a pre-experimental one-shot case study design. The sample consisted of 10 children from group B. The treatment was conducted through four learning activities using loose parts materials, followed by a posttest assessing four indicators of creativity: fluency, flexibility, originality, and elaboration. The normality test showed a significance value of 0.200 > 0.05, indicating that the data were normally distributed. The one-sample t-test showed that the calculated t-value of 6.62 was higher than the t-table value of 2.262, indicating that Hâ‚€ was rejected and Hâ‚ was accepted. The results of the creativity indicators showed that most children were in the categories of Developing Very Well and Developing as Expected. The children were able to generate diverse ideas, use materials flexibly, produce original works, and add details based on their imagination. Therefore, the use of loose parts media in learning had a positive effect on the creativity of 5–6-year-old children in the context of this study. However, because this study used a one-shot case study design with a limited sample size, the findings should be interpreted contextually and should not be generalized broadly.